Gender sensitivity of Catholic High School teachers in Iloilo City - Alimajen, Elve Joy.; Calero, Stella Marie; Dalisay, Sharon Rose.; Estorpe, Mae.; Lorque, Stella Marie (2000.)
Executive summary - The researchers conducted a study entitled "Gender Sensitivity on Catholic High School Teachers in Iloilo City." This research chose this study primarily to help the government disseminate information about gender sensitivity of the teachers in Catholic high schools. This would enable the teachers to be aware of the importance of being gender sensitive on teaching their students and how the former interact with the latter that will also lead to effective teaching. This study could also eliminate biases on the students as well as the teachers and open up their minds on all sides of life. Based on the frequency distribution of the respondents derived from the percentage analysis, most of the Catholic high school teacherss have a low gender sensitivity level. This is due to some factors such as age, civil status, gender, educational attributes, permanent address and working experience. Thus, the researchers recommend that both government and the educational institution should focus their issues on gender sensitivity by conducting training, seminars, workshop and information drive of gender sensitive and also the application of this knowledge to the development of the society.
Research Paper (Mgt 200-Management Research) -- [Iloilo City] : University of the Philippines in theVisayas-College of Management, March 2000.